Ninh Thế Quang Nhật
26 tháng 2 2017 lúc 14:46

\(A=\frac{\left(3\frac{1}{15}+\frac{1}{5}\right):2\frac{1}{2}}{\left(5\frac{3}{7}-2\frac{1}{4}\right):4\frac{43}{56}}=\frac{\left(\frac{46}{15}+\frac{3}{15}\right):\frac{5}{2}}{\left(\frac{38}{7}-\frac{9}{4}\right):\frac{267}{56}}=\frac{\frac{49}{15}.\frac{2}{5}}{\frac{89}{28}.\frac{56}{267}}=\frac{\frac{98}{75}}{\frac{2}{3}}=\frac{49}{25}\)

\(B=\frac{1,2:\left(1\frac{1}{5}.1\frac{1}{4}\right)}{0.32+\frac{2}{5}}=\frac{\frac{6}{5}:\left(\frac{6}{5}.\frac{5}{4}\right)}{\frac{8}{25}+\frac{10}{25}}=\frac{\frac{6}{5}.\frac{4}{6}}{\frac{18}{25}}=\frac{\frac{4}{5}}{\frac{18}{25}}\)

ĐỀ SAI

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN